Chronicle of the 8th March. Women’s Equality Day organized by the Spanish Association of Labour Law - Redondo Torres , Daniel; Otero Ruíz de Alegría, María (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
The present chronicle compiles the speeches presented at the 8th of March - Women’s Equality Day organized by the Spanish Association of Labour Law, dedicated to the new regulation of equality by Law 15/2022, Integral for equal treatment and non-discrimination.